Jejak Megalitik Di Desa Mayong, Buleleng Dan Potensinya Sebagai Sumber Belajar Sejarah Di SMA - Putu, Putu Intan Novitalia; Pageh, I Made; Yasa, I Wayan Putra (Widya Winayata : Jurnal Pendidikan Sejarah, 2024)
Megalithic is a form of heritage in the form of large stones that spread quite widely in Indonesia and one of them is in Buleleng, Mayong Village. In Mayong Village, several megalithic relics were found, such as: sarcophagus, megalithic statues, and large stones (monoliths). This study was conducted by the researcher to examine the megalithic traces in Mayong Village and its potential as a source of learning history in high school. This research uses historical research methods with stages: Heuristics, Source Criticism, Interpretation, and Historiography. The results showed that: megalithic relics still exist today in Mayong Village, because megalithic relics are still respected and considered a form of worship to ancestors with the mixing of Hinduism that entered Mayong Village. Megalithic remains that still exist today in Mayong Village, namely: sarcophagus, megalithic statues and large stones (monoliths). Sarcophagus is a stone burial place where 2 sarcophagi were found in Poh Asem. Then the megalithic statue is a chunk of stone carved in the shape of a human being which the villagers highly respect the statue because they consider it a manifestation of ancestral spirits. Finally, the implementation of megalithic traces in Mayong Village as a source of learning history in high school using the PJBL method, teachers are expected to implement megalithic traces in Mayong Village into teaching materials so that they can be used as local history learning. Keywords : Megalithic Age, Megalithic Remains, Learning Resources